On immigration and refugees / Michael Dummett. - Dummett, Michael, 1925- (Thinking in action, 2001)
Exploring the confused, and often highly unjust, thinking about immigration, Sir Michael Dummett questions the principles and justifications governing state policies, pointing out that they often conflict with the Geneva Convention.